High-Performance Telescope System Design for Space-Based Gravitational Waves Detection - Huiru Ji; Lujia Zhao; Zichao Fan; Rundong Fan; Jiamin Cao; Yan Mo; Hao Tan; Zhiyu Jiang; Donglin Ma (Sensors)
Space-based gravitational wave (GW) detection employs the Michelson interferometry principle to construct ultra-long baseline laser interferometers in space for detecting GW signals with a frequency band of 10−4–1 Hz. The spaceborne telescope, as a core component directly integrated into the laser link, comes in various configurations, with the off-axis four-mirror design being the most prevalent. In this paper, we present a high-performance design based on this configuration, which exhibits a stable structure, ultra-low wavefront aberration, and high-level stray light suppression capabilities, effectively eliminating background noise. Also, a scientifically justified positioning of the entrance and exit pupils has been implemented, thereby paving adequate spatial provision for the integration of subsequent optical systems. The final design realizes a wavefront error of less than λ/500 in the science field of view, and after tolerance allocation and Monte Carlo analysis, a wavefront error of less than λ/30 can be achieved with a probability of 92%. The chief ray spot diagram dimensions are significantly small, indicating excellent control of pupil aberrations. Additionally, the tilt-to-length (TTL) noise and stray light meet the stringent requirements for space-based gravitational wave detection. The refined design presented in this paper proves to be a more fitting candidate for GW detection projects, offering more accurate and rational guidance.